The role of the discipline «Foreign language» in developing a professional communicative identity in the system of higher education - Lushchynskaya, Volha V.; Savich, Alena V. (Journal of the Belarusian State University. Journalism, 2019)
The article considers issues related to the development of the professional communicative (discourse) identity in the system of higher education using foreign language as a means of achieving this goal. Competences (a system of knowledge, skills and abilities) necessary for the future specialists in their professional activity are specified and edited. Methodological bases of the discourse approach are defined and its foundations as applied to teaching foreign languages in the system of higher education are described. The focus is made on the necessity to consider the key category of «communicative situation», being treated as a holistic unity of its linguistic and extralinguistic features, while designing the process and content of teaching students to interact in a foreign language environment.